New Approaches to the Treatment of Canine Pneumonia - Sukiasyan, K. A.; Nikoghosyan, E․ A․; Abovyan, A. Yu.; Yesayan, T. Ye․ (ՀԱԱՀ հիմնադրամ)
The main goal of this study is to develop an effective method for the treatment of pneumonia in dogs. Clinical and hematological studies of the dogs sick with pneumonia as well as bacteriological examination of sputum were carried out to determine the bacterial composition and the sensitivity to antibiotics. Our recommended approach on the use of Moxifort, Gamavit, and ACC has manifested a high therapeutic effect.
Keywords: Veterinary Science and Animal Breeding